Evaluation of Thiol Homeostasis in Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorders - Arslan, Burak; Arslan, Gökçe Ayhan; Tuncer, Aslı; Karabudak, Rana; Dinçel, Aylin Sepici (Frontiers in Neurology, 2021)
Abstract Objectives: The aim of this pilot study was to evaluate dynamic thiol-disulfide homeostasis as a novel oxidative stress parameter in multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) to better understand the role of thiol homeostasis in neuroimmunological diseases. Methods: A total of 85 participants were included in this study, consisting of 18 healthy controls, 52 patients diagnosed with MS, seven with NMOSD, and eight with MOGAD. We measured total thiol (-SH+-S-S-) and native thiol (-SH) levels in the serum of all the participants, and in a subset of patients (n=11), these parameters were investigated in paired cerebrospinal fluid (CSF) and serum samples. Dynamic disulfide concentrations were calculated separately. Finally, we determined if there was any relationship between clinical features and dynamic thiol homeostasis. Results: There was a statistically significant difference between serum and CSF levels of biomarkers of thiol homeostasis. Serum total thiol (317.88 ± 66.04) and native thiol (211.61 ± 44.15) levels were significantly lower in relapsed patients compared to those in remission (368,84 ±150,36 vs 222,52 ±70,59; respectively). Conclusions: Oxidative stress plays a crucial role in the physiopathology of neuroimmunological diseases. Thiol homeostasis may be useful for monitoring disease activity. Keywords : Multiple Sclerosis, Neuromyelitis Optica Spectrum Disease, Myelin oligodendrocyte glycoprotein, Thiol, Oxidative Stress